A new Toxodontidae (Mammalia, Notoungulata) from the upper Pliocene–lower Pleistocene of Uruguay. Issue 5 (30th March 2022) - Ferrero, Brenda S.; Schmidt, Gabriela I.; Pérez-García, María I.; Perea, Daniel; Ribeiro, Ana M.
ABSTRACT: A specimen of Toxodontidae from the upper Pliocene–lower Pleistocene of Uruguay is studied in this paper. The material consists of associated skull and mandibular fragments previously identified as Dinotoxodon paranensis . The full description of the specimen, its comparison with different notoungulates, and a phylogenetic analysis are performed. According to the obtained results, Charruatoxodon uruguayensis, gen. et sp. nov. is recognized as a new taxon with unique features such as nasals compressed laterally, somewhat convex in transversal and longitudinal planes, incisive foramina deep and rounded, and other characteristics shared with several taxa of Toxodontidae. The mandibular expansion, present in the studied material, formerly used as a diagnostic character of D. paranensis (also present in Gyrinodon quassus, Pericotoxodon platignathus, and Hoffstetterius imperator ), does not constitute a synapomorphy for these taxa as it appears to have evolved independently in different lineages according to our phylogeny. The new taxon is a medium-sized toxodontid more closely related phylogenetically to Toxodon platensis and D. paranensis than to other toxodontids. The family Toxodontidae constitutes a natural group. The clades within this group do not correspond to the subfamilies classically considered within the family, agreeing with later results. The new late Pliocene–early Pleistocene taxon from the Raigón Formation adds to the endemic fauna from Uruguay.